2003
DOI: 10.1161/01.cir.0000093277.20968.c7
|View full text |Cite
|
Sign up to set email alerts
|

Cariporide (HOE642), a Selective Na + -H + Exchange Inhibitor, Inhibits the Mitochondrial Death Pathway

Abstract: Background— The Na + -H + exchanger figures prominently in cardiac ischemia-reperfusion injury. Several experimental and clinical studies have demonstrated a cardioprotective effect of Na + -H + exchanger inhibition; however, the precise mechanisms have not been established. Methods and Results— We examined the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 39 publications
(32 reference statements)
9
77
1
1
Order By: Relevance
“…In good agreement with our results, 10 μM cariporide has been previously demonstrated to attenuate the H 2 O 2 -induced increase in cytosolic and mitochondrial Ca 2+ in rat cardiomyocytes (Teshima et al, 2003). KR-32570 also significantly recovered the large reduction in ΔΨ m and cytochrome c release induced by hypoxia.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In good agreement with our results, 10 μM cariporide has been previously demonstrated to attenuate the H 2 O 2 -induced increase in cytosolic and mitochondrial Ca 2+ in rat cardiomyocytes (Teshima et al, 2003). KR-32570 also significantly recovered the large reduction in ΔΨ m and cytochrome c release induced by hypoxia.…”
Section: Discussionsupporting
confidence: 92%
“…Our results that 30 μM ruthenium red inhibited mitochondrial Ca 2+ overload during hypoxia and decreased the number of TUNELpositive cells (Fig. 5), further support the pro-apoptotic role of mitochondrial Ca 2+ during hypoxia (Teshima et al, 2003). Our results further showed that treatment with ruthenium red during hypoxia prolonged the maintenance of the elevated level of cytosolic Ca 2+ over 2 h of hypoxia.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Neonatal rat cardiac myocytes (NRCMs) were isolated from 1-2 day old Sprague-Dawley rats and cultured according to a well characterized protocol [24][25][26][27][28]. The first four days of culture medium contained the anti-mitotic, BrdU (0.1 mmol/L), to inhibit fibroblast growth in addition to 5% fetal bovine serum, penicillin/streptomycin, and vitamin B 12 .…”
Section: Neonatal Rat Cardiac Myocyte Isolation and Culturementioning
confidence: 99%
“…13 Cells were loaded with TMRE (Invitrogen) (100 nmol/L) at 37°C for 30 min. After 1 h pretreatment with pravastatin (10 nmol/L), scanning began with the application of H2O2 (100 μmol/L), and TMRE fluorescence intensity was measured every 1 min (568-nm line of a HeNe laser).…”
Section: Assays For Mitochondrial Inner Membrane Potential (∆ψM)mentioning
confidence: 99%